Manajemen Praktik Kerja Lapangan Dalam Meningkatkan Kompetensi Siswa Sekolah Menengah Kejuruan - Tyas Arianti; Afni Ma'rufah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Field Work Practice (PKL) is a form of learning in SMK education institutions that must be followed by all students. Through street vendors activities students can practice directly regarding the knowledge they have acquired at school and also acquire new knowledge from outside the school and can improve the competence of students. The PKL program includes management of Field Work Practices (PKL) which is a process of managing, directing, and regulating PKL activities by utilizing all available resources so that the PKL program objectives can be easily implemented and achieve success. This research uses qualitative methods by obtaining data through interviews, observation, and documentation. The subjects in this study included school principals, deputy heads of curriculum, deputy heads of public relations, heads of expertise programs, and students of SMKN 1 Ponorogo. Based on the results of the study, 1) Field Work Practice Management at SMKN 1 Ponorogo begins with planning, implementation and evaluation activities. PKL planning is carried out by assessing the location of the street vendors, distributing places and mentors, as well as providing student training. Implementation of street vendors, namely students carry out street vendor activities in predetermined locations and are required to comply with regulations and carry out tasks given by the school. Finally, evaluation, in this case an assessment is carried out related to how the street vendors are implemented, whether it has gone according to expectations and identified various obstacles that have occurred so that it can be used as learning for the implementation of the street vendors program in the next period. 2) The competence of students has increased after carrying out street vendors, both in terms of knowledge, skills and attitudes. One of these things can be known from the comparison of the results of student scores before and after street vendors